Additive Manufacturing of Co-Cr-Mo Alloy: Influence of Heat Treatment on Microstructure, Tribological, and Electrochemical Properties - Mantrala, Kedar Mallik; Das, Mitun; Balla, Vamsi Krishna; Rao, Ch. Srinivasa; Kesava Rao, V. V. S. (Frontiers in Mechanical Engineering, 2015)
Co-Cr-Mo alloy samples, fabricated using Laser Engineered Net Shaping – a laser based additive manufacturing technology, have been subjected heat treatment to study its influence on microstructure, wear and corrosion properties. Following L9 Orthogonal array of Taguchi method, the samples were solutionized at 1200oC for 30, 45 and 60 min followed by water quenching. Ageing treatment was done at 815oC and 830oC for 2, 4 and 6 h. Heat treated samples were evaluated for their microstructure, hardness, wear resistance and corrosion resistance. The results revealed that highest hardness of 512 ± 58 Hv and wear rate of 0.90 ± 0.14 × 10-4 mm3/N.m can be achieved with appropriate post-fabrication heat treatment. ANOVA and grey relational analysis on the experimental data revealed that the samples subjected to solution treatment for 60 min, without ageing, exhibit best combination of hardness, wear and corrosion resistance.